Lpv Modeling and Control for the Aeropendulum System - Acosta-Barbosa, K; Zoulagh, T (Institute of Electrical and Electronics Engineers Inc., 2023)
This work focuses on the control of an aeropendulum system an unattached pendulum with a fixed end, allowing for the application of a controlled moment to regulate its angular position. It encompasses both control theory and practical application using a physical aeropendulum setup. Initially, we propose a linear parameter varying (LPV) model for the system. Subsequently, we design an LPV H∞ controller and a PID controller to regulate the pendulum s angular position precisely. To assess the performance of these designed controllers, we conducted comparisons through simulations and implemented them in a physical plant within a laboratory setting. © 2023 IEEE.